Influence of hydrogen plasma treatment on secondary phases in CZTS thin films for energy harvesting. (September 2021) - Babichuk, Ivan S.; Semenenko, Mykola O.; Caballero, Raquel; Hladkovskyi, Volodymyr V.; Datsenko, Oleksandr I.; Yeshchenko, Oleg A.; Babichuk, Iryna V.; Lin, Chubin; Qiu, Yuhui; Redko, Roman A.; Hreshchuk, Oleksandr M.; Yukhymchuk, Volodymyr O.; et al.
Abstract: Cu2 ZnSnS4 (CZTS) thin films deposited using direct current magnetron sputtering and sulfurized at argon atmosphere pressures of 950, 460, and 50 mbar are studied in a view of solar cell absorber fabrication. The main novelty in the work is the influence of the radio frequency (RF) electromagnetic field treatment on the Cu2−x S secondary phase. The treatment reduces the amount of the Cu2−x S secondary phase, which is confirmed by Raman spectroscopy. The RF effect is long-term, at least one year later. So, this treatment is a promising technique to achieve higher purities of CZTS absorber layers for solar cells. Graphical Abstract: ga1 Highlights: An influence of RF treatment on the Cu2−x S secondary phase in CZTS films was studied. A loss of the Cu2−x S was detected after RF treatment of all CZTS films in H + plasma. This effect is long-term and relevant in the creation of thin CZTS films.